Studying dislocation-induced shielding effect on the crack-tip in polycrystal by discrete dislocation dynamics. (January 2019) - Liang, Shuang; Zhu, Yaxin; Huang, Minsheng; Li, Zhenhuan
Abstract: The dislocation-induced shielding effect on the crack-tip depends on not only the number of dislocations but also the distance of dislocations from the crack-tip. The former is closely related to the nucleation of dislocation but the latter to the grain size and the obstruction of grain boundaries (GBs) to dislocations. In this paper, a discrete dislocation dynamic framework was further developed with a crack-tip dislocation emission scheme especially introduced, and then a series of discrete dislocation dynamic simulations were performed to study the shielding effect of dislocations on the crack-tip in poly-crystals. The different roles of the dislocation nucleation from the Frank-Read sources (DNFR) and dislocation emission from the crack-tip (DECT) in the shielding effect were studied, which indicates the DECT mechanism plays more important role compared with the DNFR one for the cases considered here. The shielding effect of dislocation is dominated by the grain size as well as the energy barrier for dislocation transmission across GB. With the increase of grain size, the shielding effect of dislocations on the crack-tip increases significantly, showing strong grain size effect. Moreover, with the increase of the GB energy barrier for dislocation transmission, the shielding effect of dislocations on the crack-tip first increases and then reaches its peak and finally decreases, showing an interesting mountain-shaped dependence on the GB energy barrier. This mountain-shaped dependence is gradually flattened with the increases of grain size. These interesting results enrich our understanding of the dislocations-induced shielding effect on the crack-tip in the poly-crystals. Graphical abstract: